A profissional enfermeira frente as influências da evolução histórica da mulher - Sônia Regina Coradini; Rosmari Barbiani (Associação Brasileira de Enfermagem, 1983)
This bibliographical study shows the origins of woman's historical opression as much as the factors the influence her as abeing and as a professional worker. It analyzes thet repercussion of social, political and economical factors establishing a relationshi with nursing that is formed in its majority by women. At end of this study we show the stages of woman's evolution in nursing, her historical professional subjection. It proposes as opcions: 1.º To get conscious of her situation; 2.º Possible ways of actuation as a professional worker; 3.º And, nowadays, the legalization of her work and the nursing process as a means to acquire professional autonomy.